An approach using a low-code platform for retraining professionals to ICT - Metrôlho, J.C.M.M. (2019)
Submitted by Jose Carlos Metrolho (metrolho@ipcb.pt) on 2019-09-05T10:35:16Z No. of bitstreams: 1 EDULEARN_1719.pdf: 247249 bytes, checksum: 92ce4cf71b5e3ab6ededef9f72a87718 (MD5)